Evaluated thermoluminescence trapping parameters–What do they really mean?. (August 2016) - Chen, R.; Pagonis, V.; Lawless, J.L.
Abstract: The main two trapping parameters in thermoluminescence (TL), the activation energy and the frequency factor, are often calculated and used for the evaluation of the stability of the TL signal at a given temperature. In several cases, "anomalous" values of these parameters, either very high or very low have been reported in the literature. In practically all of these cases, the values reported have been recognized to be effective values which resulted from some special circumstances related to the specific materials in hand. Obviously, these effective values are not associated directly with the real rate of thermal release of carriers from traps at the ambient temperature, prior to heating, and therefore, they do not indicate the real decay time of the TL signal or, in other words, the stability of the signal which may be used in TL dosimetry or dating of archaeological or geological samples. In the present paper, we discuss briefly some of these cases and add, in more detail, a rather elementary situation of very low effective activation energy and frequency factor. A model with two trapping states and one kind of recombination center is used and the simulation includes the numerical solution of the relevant sets of coupled differential equations in the three stages of the measurement, namely, excitation, relaxation and heating for a given set of the trapping parameters. The parameters are chosen in such a way that two overlapping TL peaks occur, which look together like a single first-order peak, but with anomalously low evaluated effective activation energy and frequency factor. Implications regarding the possible results in glow curve deconvolution are discussed. Highlights: Double TL peak may look like a single peak. Simulated double peak analyzed by peak-shape methods and by deconvolution. Determination of effective activation energies and frequency factors. Effect of anomalous stability predicted.